Products of Factorial Schur Functions - Kreiman, Victor (The Electronic Journal of Combinatorics, 2008)
The product of any finite number of factorial Schur functions can be expanded as a Z[y]-linear combination of Schur functions. We give a rule for computing the coefficients in such an expansion. This rule generalizes the classical Littlewood-Richardson rule and several special cases of the Molev-Sagan rule.